Validation of Two US Risk Scores for Percutaneous Coronary Intervention in a Single-Center Portuguese Population of Patients with Acute Coronary Syndrome - Timóteo, AT (2016)
INTRODUCTION: New scores have been developed and validated in the US for in-hospital mortality risk stratification in patients undergoing coronary angioplasty: the National Cardiovascular Data Registry (NCDR) risk score and the Mayo Clinic Risk Score (MCRS). We sought to validate these scores in a European population with acute coronary syndrome (ACS) and to compare their predictive accuracy with that of the GRACE risk score. METHODS: In a single-center ACS registry of patients undergoing coronary angioplasty, we used the area under the receiver operating characteristic curve (AUC), a graphical representation of observed vs. expected mortality, and net reclassification improvement (NRI)/integrated discrimination improvement (IDI) analysis to compare the scores. RESULTS: A total of 2148 consecutive patients were included, mean age 63 years (SD 13), 74% male and 71% with ST-segment elevation ACS. In-hospital mortality was 4.5%. The GRACE score showed the best AUC (0.94, 95% CI 0.91-0.96) compared with NCDR (0.87, 95% CI 0.83-0.91, p=0.0003) and MCRS (0.85, 95% CI 0.81-0.90, p=0.0003). In model calibration analysis, GRACE showed the best predictive power. With GRACE, patients were more often correctly classified than with MCRS (NRI 78.7, 95% CI 59.6-97.7; IDI 0.136, 95% CI 0.073-0.199) or NCDR (NRI 79.2, 95% CI 60.2-98.2; IDI 0.148, 95% CI 0.087-0.209). CONCLUSION: The NCDR and Mayo Clinic risk scores are useful for risk stratification of in-hospital mortality in a European population of patients with ACS undergoing coronary angioplasty. However, the GRACE score is still to be preferred.